An Interface-Based Method for Performance Improvement of the Municipal Solid Waste - Tabukeli, Musigi Ruhiiga; Virginia, Nthavheleni Mudau (MUST Journal of Research and Development (MJRD), 2023)
The municipal waste stream is evaluated within an operations context for the purpose of deploying interface management to improve performance. Using a set of nine municipalities in Limpopo Province, South Africa, stratified random sampling produced 225 observations made up of collection, treatment, and landfill sites. Field observation and repeated measurement of eight predictors and one response variable were used to collect data, followed by an experimental set of 29 sites where a three-cycle treatment of loadings was used to record changes in the response variable. A primary data set was initially entered into Excel to generate descriptive statistics. Multiple linear regression and correlation were performed using the stepwise option after testing for normality and collinearity. The results show statistically significant final models (F (1,221) = 1093.23, 105.77, p.001), with an adjusted R2 of.040 and a 95% confidence level. Technical and managerial problems in waste management are critical at interfaces that provide ideal sites for targeted interventions to accelerate the rates of waste flow to landfills. The contribution of the study lies in the development of an interface-based method for improving the performance of the waste stream. The implications speak to issues of waste management that feed into concerns about sustainable urbanisation today.